Contributing and mitigating factors of brain drain among healthcare workers from cardiac care facilities in Nepal - A qualitative case study. - Niharika Jha; Rashmi Maharjan; Swornim Bajracharya; Soniya Shrestha; Bobby Thapa; Pranil Man Singh Pradhan; Sushmita Mali; Biraj Man Karmacharya; Archana Shrestha (PLOS Global Public Health)
The migration of health experts seeking better opportunities, both nationally and internationally, is a growing concern due to its impact on health systems, particularly in developing countries. The provision of cardiovascular and other specialized medical care requires a skilled workforce, yet the factors driving brain drain among cardiac care health workers remain underexplored. This study assessed the factors influencing the brain drain of cardiac healthcare workers from the perspective of the health policymakers and health care workers in Nepal. We conducted a cross-sectional qualitative study among 32 key informants selected purposely working at the policy level, tertiary cardiac care hospitals, universities, cardiac care civil societies, and medical, nursing, and public health professional councils in Nepal. We interviewed the participants using a standardized key informant interview guide with open-ended questions probing for in-depth information in the Nepali language. The interviews were audio-recorded, transcribed, coded, and analyzed using the thematic method. We used the inductive method of data analysis and manually developed codes and themes from the transcripts ensuring a robust analysis of the migration factors impacting cardiac healthcare workers. Key findings revealed several contributing factors to brain drain, including better job opportunities, higher pay scales, and improved working environments in developed countries. Push factors such as young age, family attitudes toward migration, and low levels of patriotism among healthcare professionals were also identified. Addressing these issues requires targeted retention strategies, including creating opportunities within the country, fostering collaboration between policymakers and stakeholders, and enhancing working conditions in Nepal's healthcare sector. The global public health implications of brain drain are significant, underscoring the need for sustainable solutions to strengthen healthcare systems and promote health equity. Developing and implementing policies that mitigate brain drain will be crucial to retaining skilled cardiac healthcare workers and ensuring the delivery of quality care in Nepal.